DAMPAK MODEL QUANTUM TEACHING TERHADAP HASIL BELAJAR PADA PEMBELAJARAN IPS PESERTA DIDIK - Vani Qhairum Nisa Utami; Firman; Desyandri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This research is a quantitative study that aims to determine the impact of the Quantum Teaching learning model on student learning outcomes conducted at SD Negeri 09 Bandar Buat 2022/2023. The method used is descriptive method. The population of this study were all fourth grade students of SD Negeri 09 Bandar Buat consisting of one class with 30 students. The results showed that the Quantum Teaching model was in the good category with an average of 80.7, the correlation coefficient of 0.705 means (0.705) rhitung ≥ rtabel (0.361) then ha is accepted. Hypothesis testing shows thitung > ttabel namely 6.363 ≥ 1.697, thus stating that ha is accepted.